A case study on the crisis management strategies of Tacurong City Peace and Order Council (TCPOC) on the Maguindanao Massacre (2009) and the Tacurong City roadside car bombing (2011) - Dimaano, Ariesha Faith M.
Crisis management is a process an organization must undergo whenever any action or event may threaten them, their stakeholders, or the people they protect. This study was conducted to identify the crisis management strategies of the Tacurong City Peace and Order Council (TCPOC) on the Maguindanao Massacre and the Tacurong City Roadside Car Bombing and analyze them through Coombs?s Three-Phase Crisis Management Model and Hersey and Blanchard?s Situational Leadership Theory. The researcher?s primary data came from the interviews with Chairperson of the SP Committee on peace and Order Rodrigo Jamorabon. The data gathered were classified into pre-crisis, crisis and post-crisis respectively and were compared using Nikolaev?s 30 Common Basic Elements of Crisis Management Plans. It illustrated that these crisis differ in proximity, established degree of danger, and organizational role during the incidents. TCPOC, as a leading organization for security and protection, was also found out to be the type who disseminates information and tasks to other subgroups appropriate for the kind of crisis. The observable change in have indicated that they matured with regard to decision-making and task and relationship behaviors. It was also emphasized that communication plays a vital role for an effective crisis management: to serve as the link force; to share accurate information; to manage messages and to neutralize tension. Finally, the researcher derived a model presenting communication and security as the key factors to manage the presented crises. It is through these factors that locale issues, public reaction, and fear in political disputes can be addressed.